Monitoring strategy for relay incentive mechanism in cooperative communication networks. (May 2017) - Zhao, Nan; Chen, Yang; Liu, Rui; Wu, Minghu; Xiong, Wei
Highlights: A contract-based relay incentive mechanism is investigated under the dual asymmetric network information scenario. The optimal contract design is proposed to achieve the twin objectives of ability-discrimination and effort-incentive. Considering the feature of asymmetric information, the optimal contract designs with the non-monitoring, the information-monitoring, and the action-monitoring strategies are presented. Graphical abstract: Abstract: Cooperative communication is a promising technique to improve wireless network's capacity and resource management's efficiency. However, due to the limited wireless network resource, the potential selfish relay nodes may not be willing to cooperate without any extra incentives. In this paper, a contract-based relay incentive mechanism is investigated under the dual asymmetric network information scenario. The optimal contract design is proposed to achieve the twin objectives of ability-discrimination and effort-incentive . Considering the feature of asymmetric information, the various monitoring strategies are designed by introducing a monitoring node. The optimal contract designs with the information-monitoring and the action-monitoring strategies are presented. Simulation results show that the optimal contract design effectively incentivizes relay nodes' participation, and the performance of the action-monitoring strategy yields a significant enhancement compared with the non-monitoring and the information-monitoring strategies.